Histological and morphometric comparisons of worker and queen mandibular glands of Melipona bicolor bicolor (Hymenoptera, Meliponini) - Gracioli, Luciana Fioretti [UNESP]; Silva de Moraes, Regina Lúcia Morelli [UNESP] (My University, 2002)
In the present investigation we analyzed both histology and area of secretory cells from workers, virgin and physogastric queen mandibular glands of Melipona bicolor bicolor Lepeletier. The histological differences observed include the number of vacuoles present in the cell cytoplasm and the quantity and distribution of the secretion. The morphometry results demonstrated the occurrence of significative differences in the cell area values that were related to the secretory cell activity level, which is higher in the physogastric queens. Worker and queen glands have histological patterns quite similar, but the morphometric data indicated cast-specific differences, as well as differences between the queens, which were related to the posture activity.
Keywords: Hematoxylin-eosin; Mandibular glands; Melipona bicolor; Morphometry